Electrochemical disinfection of irrigation water with a graphite electrode flow cell. (28th September 2020) - Qing, Geletu; Anari, Zahra; Foster, Shelby L.; Matlock, Marty; Thoma, Greg; Greenlee, Lauren F.
Abstract: In this work, we report experimental studies on the disinfection of irrigation water using a flow cell assembled with low‐cost graphite plates as both anode and cathode. Natural irrigation waters collected from two irrigation locations (Reservoir 225 and Bott Well Pond) in Hawaii were used, and synthetic irrigation waters were prepared based on the chemical analysis of natural irrigation waters. The concentration of chloride was 10.2 mg/L in the synthetic Reservoir 225 water and 6.9 mg/L in the synthetic Bott Well pond water. Escherichia coli K12 ER2738 was selected as a model bacterium to evaluate the disinfection capability of the flow cell. Experiments performed in the synthetic irrigation waters showed that E. coli was inactivated by free chlorine species electro‐generated from oxidation of chloride ions at the graphite anode. Complete removal of E. coli was achieved within 10 min in the synthetic irrigation waters. The disinfection of the natural irrigation waters took about four times longer than the disinfection of the synthetic irrigation waters. This result is most likely due to the presence of organic matter (and possibly other oxidizable species) in the natural irrigation waters. Practitioner points: Electrochemical flow cell disinfects to 99.9% with commercial graphite electrodes. E. coli is removed in 10 min from synthetic irrigation water by a flow cell. E. coli removal takes 4× longer in natural irrigation water. A minimum current density of ≥1 mA/cm 2 is required for disinfection. The primary disinfection mechanism is through chlorine generated from chloride ions. Abstract : A two‐electrode electrochemical flow cell is demonstrated to disinfect synthetic and natural irrigation waters through hypochlorite generation at the anode.